Training environment and sponsorship dynamics in Hungarian artistic swimming - Máté, Domicián; Vveinhardt, Jolita; Fekete, Anna (Frontiers in Sports and Active Living, 2024)
The present study examines the training environment and sponsorship dynamics in Hungarian artistic swimming, with a particular focus on competitiveness. Through the utilization of a linear regression method ample aspects were identified, such as coach qualifications, funding sources, and facilities, that positively impact the number of qualified competitors. The availability of funding sources, when coupled with governmental assistance, has a favorable effect on the number of competitors, whereas membership fees have a deleterious impact. Furthermore, the findings indicate that increased water availability and increased publicity enhance artistic swimming recognition, whereas improved land-based training conditions may lead to a decline in the number of competitors. This paper discusses how different aspects of training programs can be integrated to improve overall athleticism, prevent injury, and enhance the competitive ability of artistic swimmers.